Developing densified products to reduce transportation costs and improve the quality of rice straw feedstocks for cattle feeding - Ngo, Thi Thanh Truc; Ho, Vu Khanh; Tran, Sy Nam; Duong, Van Chin; Nguyen, Van Cong; Nguyen, Van Hung (Technische Universität Dresden, 2020)
This study resulted in a comparative analysis of greenhouse gas emissions (GHGE) for rice production with different in-field rice straw management practices based on an experiment conducted in An Giang Province of Vietnam, during the autumn - winter season of 2016. Direct field GHGE was analyzed based on in-situ measurement and the total direct and indirect GHGE were estimated by applying the life cycle assessment using Ecoinvent3 database which is incorporated in SIMAPRO software. The experiment was conducted based on a completely random design with three treatments and three replications. The three treatments are [T1] Incorporation of straw and stubbles treated with Trichoderma; [T2] Incorporation of stubbles and removal of straw; and [T3] In-field burning straw. Closed chamber protocol and gas chromatography (SRI 8610C) was used to measure and analyse CH4 and N2O. CH4 emission rate was not significantly different (p>0.05) among the three treatments during sampling dates except on the days 17 and 24 after sowing (DAS). N2O emission rate was not significantly different (p>0.05) either. However, there were high variations of N2O emission after the dates of urea applied. Direct field emissions of CH4, N2O and CO2 equivalent (CO2eq) are not significantly different among the three treatments, but the amount of CO2eq per kg straw in T1 of incorporating rice straw treated with Trichoderma is significantly higher than in T3 of in-field burning straw. LCA based analysis resulted in total GHGE in the range of 1.93-2.46 kg CO2-eq kg-1 paddy produced consisting of 53-66% from direct soil emissions. Incorporation of straw treated with Trichoderma did not indicate the improvement of paddy yield. However, the organic matter, N-NH4+, and N-NO3- of this treatment was higher than those of the other researched treatments. This research was just conducted in one crop season, however, the results have initial implications for the other crop seasons.